RPS Brazilian Birth Cohorts Consortium (Ribeirão Preto, Pelotas and São Luís): history, objectives and methods - Susana Cararo Confortin; Marizélia Rodrigues Costa Ribeiro; Aluísio J. D. Barros; Ana Maria Baptista Menezes; Bernardo L. Horta; Cesar Gomes Victora; Fernando C. Barros; Helen Gonçalves; Heloisa Bettiol; Iná Silva dos Santos; Marco Antonio Barbieri; Maria da Conceição Pereira Saraiva; et al. (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2021)
Abstract: This paper describes the history, objectives and methods used by the nine Brazilian cohorts of the RPS Brazilian Birth Cohorts Consortium (Ribeirão Preto, Pelotas and São Luís) Common thematic axes are identified and the objectives, baseline periods, follow-up stages and representativity of the population studied are presented. The Consortium includes three birth cohorts from Ribeirão Preto, São Paulo State (1978/1979, 1994 and 2010), four from Pelotas, Rio Grande do Sul State (1982, 1993, 2004 and 2015), and two from São Luís, Maranhão State (1997 and 2010). The cohorts cover three regions of Brazil, from three distinct states, with marked socioeconomic, cultural and infrastructure differences. The cohorts were started at birth, except for the most recent one in each municipality, where mothers were recruited during pregnancy. The instruments for data collection have been refined in order to approach different exposures during the early phases of life and their long-term influence on the health-disease process. The investigators of the nine cohorts carried out perinatal studies and later studied human capital, mental health, nutrition and precursor signs of noncommunicable diseases. A total of 17,636 liveborns were recruited in Ribeirão Preto, 19,669 in Pelotas, and 7,659 in São Luís. In the studies starting during pregnancy, 1,400 pregnant women were interviewed in Ribeirão Preto, 3,199 in Pelotas, and 1,447 in São Luís. Different strategies were employed to reduce losses to follow-up. This research network allows the analysis of the incidence of diseases and the establishment of possible causal relations that might explain the health outcomes of these populations in order to contribute to the development of governmental actions and health policies more consistent with reality.